New type surfaces in terms of B-Smarandache Curves in Sol3 (Acta Scientiarum. Technology, 2015)
Â In this work, new type ruled surfaces in terms of B- Smarandache TM1 curves of biharmonic B- slant helices in the SOL3 are studied. We characterize the B- Smarandache TM1 curves in terms of their Bishop curvatures. Additionally, we express some interesting relations.Â